Corporate Social Responsibility PT Kereta Api Indonesia (Persero) dalam Penguatan Program Sahabat Difabel - Adelia Putri; Rika Fauziana; Thresia Agnes Monica Simarmata; Siska Rahayu (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
The aim of this research is to find out the process carried out by CSR PT. KAI (Persero) in carrying out programs organized through disabled friends starting from fact finding, planning and programming, taking action and communications, evaluating. Research from this theoretical basis refers to the Four Steps of Public. Relations discovered by Cutlip, Center, and Broom. Referring to the chosen theory, it is able to construct the overall process both in formulating indicators and collecting data regarding the CSR program for friends with disabilities. The results of this research show that PT Kereta Api (Persero)'s Corporate Social Responsibility in Strengthening the Friends of Disabled Program is considered effective. Carrying out a program for the welfare of people with disabilities is an effort to build the company's image in the eyes of the community by providing services both morally and materially. Thus, through the disabled friends program, the public's perception of PT. KAI (Persero) is a company that supports and is friendly to people with disabilities.